2020
DOI: 10.1101/2020.07.17.206771
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The enrichment of breakpoints in late-replicating chromatin provides novel insights into chromoanagenesis mechanisms

Abstract: The rise of pangenomic molecular assays allowed uncovering complex rearrangements named chromoanagenesis that were hypothesized to result from catastrophic shattering events. Constitutional cases have typically been reported individually preventing identification of common features and uncovering the mechanisms at play. We characterized 20 new chromoanagenesis and discovered yet undescribed features. While literature differentiates chromothripsis and its shattering event repaired through non-homologous end joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…This patient had five segments of chromosome 1 inserted into chromosome 17q24.3, which is hypothesised to disrupt a TAD close to KCNJ2/SOX9. The rearrangement was confirmed by nanopore long-read genome sequencing and has been classified as an example of chromoanasynthesis [99] revealing a new mechanism for this rare craniofacial phenotype.…”
Section: Table 1 Structural Variants Found In the Oxclinwgs Cohortmentioning
confidence: 88%
“…This patient had five segments of chromosome 1 inserted into chromosome 17q24.3, which is hypothesised to disrupt a TAD close to KCNJ2/SOX9. The rearrangement was confirmed by nanopore long-read genome sequencing and has been classified as an example of chromoanasynthesis [99] revealing a new mechanism for this rare craniofacial phenotype.…”
Section: Table 1 Structural Variants Found In the Oxclinwgs Cohortmentioning
confidence: 88%
“…Work in preprint suggests that premature condensation of the late replication regions in micronucleus leads to either replication forks collapse (and creat DSBs) or stall (will initiate MMBIR events), so that both chromothripsis and chromoanasynthesis can be observed in micronucleated chromosomes. 93 Third, chromothripsis in chromatin bridges is frequently accompanied by kataegis (Table 1)…”
Section: Mutational Landscapes Within the Micronucleated Chromosomementioning
confidence: 99%
“…Second, it has found that copy numbers are increased at multiple loci in the micronucleated chromosomes, 24,38 suggesting chromoanasynthesis (Table 1) occurs downstream of micronucleation. Work in preprint suggests that premature condensation of the late replication regions in micronucleus leads to either replication forks collapse (and creat DSBs) or stall (will initiate MMBIR events), so that both chromothripsis and chromoanasynthesis can be observed in micronucleated chromosomes 93 . Third, chromothripsis in chromatin bridges is frequently accompanied by kataegis (Table 1).…”
Section: Mutational Landscapes Within the Micronucleated Chromosomes:mentioning
confidence: 99%